Activity of mannose-binding lectin (MBL) in centenarians - Tomaiuolo, Rossella (2012)
We analyzed MBL2 gene variants in two cohorts of centenarians, octo-and nonagenarians and in the general population, one from Sardinia island (Italy), recruited in the frame of the AKea study, and another from Campania (southern Italy), to search for haplotypes related to longevity. We also assessed in vitro the effect of mannose-binding lectin (MBL) on various human cells at different stage of senescence. The frequency of high and null activity haplotypes was significantly lower and the frequency of intermediate activity haplotype significantly higher in centenarians and in subjects between 80 and 99 years from both the cohorts as compared each to the general population from the same geographic area. Furthermore, serum MBL concentration (also after normalization to serum albumin) was significantly lower in centenarians and in octo- and nonagenarians as compared to the general population suggesting that intermediate MBL haplotype/activity may be protective. We also demonstrated that in vitro MBL protein bound to senescent IMR90 fibroblasts thereby causing cell lysis, but not to other types of cycle-arrested cells not in senescence. This implicates a novel role of MBL in the clearance of senescent cells.